Gravitational marketing : the science of attracting customers - Vee, Jimmy, 1975-; Miller, Travis, 1977-; Bauer, Joel, 1960-; Miller, Jennifer (Hoboken, N.J. : John Wiley & Sons, 2008)
If you're an entrepreneur, business owner, or sales professional, Gravitational Marketing offers a simple method for attracting customers without the hassle of traditional manual sales labor. If you want to sell more and work less, this book.
The laws of gravitational marketing. The power of gravity -- Anatomy of gravitational marketing -- How to be worthy of attraction -- The Newton in all of us -- The object of your attraction -- Increase your gravitational potential -- Creating irresistible attraction -- Gravitational marketing attraction techniques. Activate your gravitational attraction -- Attracting through personal effort -- Attracting through direct mail -- Attracting through print -- Attracting through free publicity -- Attracting through the internet -- Attracting through radio and television -- Epilogue.
Includes index.
Print version record.
English.
John Wiley and Sons
Keywords: Marketing -- Psychological aspects; Marketing -- Social aspects; Consumers -- Psychology; Information behavior; Marketing -- Aspect psychologique; Marketing -- Aspect social; Comportement dans la recherche de l'information.; BUSINESS & ECONOMICS -- Advertising & Promotion; Consumers -- Psychology; Information behavior; Marketing -- Psychological aspects; Marketing -- Social aspects